Forced and slave labor in Nazi-dominated Europe : symposium presentations - Center for Advanced Holocaust Studies (Center for Advanced Holocaust Studies, United States Holocaust Memorial Museum, 2004)
Forced and slave labor : the state of the field / Peter Hayes -- The business of genocide / Michael Thad Allen -- Cultural policy and political oppression : Nazi architecture and the development of SS forced labor concentration camps / Paul B. Jaskot -- Jewish forced labor as a basic element of Nazi persecution : Germany, Austria, and the occupied Polish territories (1938-1943) / Wolf Gruner -- The Hungarian labor service system (1939-1945) : an overview / Randolph L. Braham -- The factory slave labor camps in Starachowice, Poland : survivors' testimonies / Christopher R. Browning -- Retelling the Jewish slave labor experience in Romania / William Rosenzweig -- Forced labor along the "Strasse der SS" / Andrej Angrick -- Foreign labor in Vichy, France : the Groupements de Travailleurs Etrangers / Sarah B. Farmer -- Racism versus pragmatism : forced labor of Soviet prisoners of war in Germany (1941-1942) / Rolf Keller